Zur Reform des Straf- und Jugendverfahrensrechts in Japan - Kawasaki, Hideaki (Zeitschrift für Japanisches Recht, 2004)
Since the enactment of the Japanese Code of Criminal Procedure and the Juvenile Code in 1948 no major reforms have taken place in the field of criminal procedure law and juvenile law for almost fifty years. In the meantime, only a few changes have been brought about by decisions of the Supreme Court. In 1999 and 2000, however, for the first time the legislator resolved to undertake broad reforms. In 1999 a law was introduced that authorizes eavesdropping under specific conditions. In 2000 two laws passed the diet that aim at a better protection of the interests of crime victims. In addition, the Code of Criminal Procedure and the Juvenile Code have been amended. The reform of the Juvenile Code changed juvenile procedure so that prosecutors can be admitted to participate in the trial before the family court, and cases of more severe juvenile crimes are generally to be brought before a criminal court instead of the family court. In 2004, further reforms have taken place. By adopting two new laws, the legislator introduced a system allowing participation of lay assessors (saiban-in) in trials, and provided a new set of rules for legal aid. Moreover, another amendment of the Code of Criminal Procedure laid the legal grounds for the right of the suspect to an assigned counsel already during the preliminary proceedings. The author is quite critical about many aspects of the recent reforms. He argues that the new law that allows the Japanese police to eavesdrop private telecommunication violates the Japanese Constitution’s Art. 21 (secrecy of communication) and Art. 35 (certainty of judicial warrants). Furthermore, he rejects the reforms in juvenile law, because they constitute an undesirable step towards convergence of criminal proceedings and juvenile proceedings. There was also no reasonable justification for the recent reform and the corresponding tightening of juvenile proceedings, such as lowering the minimum age at which the juvenile can be indicted before a criminal court to the age of fourteen. Moreover, he disagrees with some aspects of the laws for the promotion and protection of victims, and the concrete alterations they brought about. He particularly criticizes the new right of victims to present their opinions and feelings in trials, arguing that this kind of measure would only be acceptable under the following circumstances: (1) if the trial was in principle divided into two parts, with one part dealing only with the fact-finding and another concentrating on the sentence; and (2) if the victim had a right only to present his or her views in the second part. This opinion is justified by pointing out that in the phase of fact-finding it is not yet clear if the accused was the offender, yet the presentation by the victim already implies the accused’s guilt. Therefore, the author argues that giving the victim the opportunity to participate in trials, in the way now provided by law, constitutes a violation of one of the basic principles of criminal procedure law, the presumption of innocence. On the other hand, he criticizes inadequate psychological, medical and financial assistance for victims in Japan, and argues that the promotion of such forms of aid is much more important than the promotion of procedural rights. Generally, the author opposes the direction the reforms seem to take. In his view, most of them have the main purpose of expanding and further promoting the efficiency of criminal prosecution. Since the legal position of defendants in Japan after the reform remains generally much too weak, he votes for the promotion of an accused’s rights in the course of criminal proceedings instead. (The Editors)